Implementasi Syllabic Method Dengan Model Connected Dalam Upaya Meningkatkan Kemampuan Membaca Permulaan Siswa Kelas I UPT SPF SD Inpres Bontomanai Kota Makassar - Indriani Muslima Jufri; Andi Adam; Maria Ulviani (Departement of Mathematics Education, 2024)
The main problem in this research is how to apply the syllabic method with a connected model to improve the reading ability of grade 1 students at UPT SPF SD Inpres Bontomanai, Makassar City. This research aims to improve the beginning reading ability of grade 1 students at UPT SPF SD Inpres Bontomanai, Makassar City by implementing the syllabic method with a connected model. This type of research is class action research (Class Action Research) which consists of two cycles, each cycle carried out in three meetings. Research procedures include planning, implementation, observation/evaluation, and reflection. The subjects in this research were 23 grade 1 students of UPT SPF SD Inpres Bontomanai, Makassar City. The results of the research showed that in the first cycle of 23 students who completed the written test, there were 10 students or 43% who met the Minimum Completeness Criteria (KKM) or were in the good category. students or 61% who meet the Minimum Completeness Criteria (KKM) or are in the sufficient category. Meanwhile, in cycle II, in the written test of 23 students, there were 23 students or 100% who met the Minimum Completeness Criteria (KKM) or were in the very good category, and in the oral test of beginning reading with the syllabic method, of the 23 students there were 22 students or 96 % who meet the Minimum Completeness Criteria (KKM) or are in the very good category. Based on the results of the research above, it can be concluded that the beginning reading ability of grade 1 students at UPT SPF SD Inpres Bontomanai Makassar City through the implementation of the syllabic method with the connected model has increased.